Return Bagi Hasil Deposito Akad Mudharabah pada Bank Umum Syariah di Indonesia Tahun 2010-2013 - Elloni Shenurti (Jurnal Manajemen, 2017)
This study the prime factors in the determination of return of mudharabah deposit on Islamic Banks in Indonesia. The independent variable used in this study is the Financing Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), rate of nisbah, rate of BI, and inflation. While return of mudharabah deposit is the dependent variable. These results indicate that the variable rate of nisbah affect positively and significantly to the return of mudharabah deposit. While the variable Financing Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), rate of BI and inflation did not significantly affect the return of mudharabah deposit.